Evaluation of controlled strain in silicon nanowire by UV Raman spectroscopy. (22nd May 2017) - Yokogawa, Ryo; Hashimoto, Shuichiro; Asada, Shuhei; Tomita, Motohiro; Watanabe, Takanobu; Ogura, Atsushi
Abstract: The evaluation of strain states in silicon nanowires (Si NWs) is important not only for the surrounding gate field-effect transistors but also for the thermoelectric Si NW devices to optimize their electric and thermoelectric performance characteristics. The strain states in Si NWs formed by different oxidation processes were evaluated by UV Raman spectroscopy. We confirmed that a higher tensile strain was induced by the partial presence of a tetraethyl orthosilicate (TEOS) SiO2 layer prior to the thermal oxidation. Furthermore, in order to measure biaxial stress states in Si NWs accurately, we performed water-immersion Raman spectroscopy. It was confirmed that the anisotropic biaxial stresses in the Si NWs along the length and width directions were compressive and tensile states, respectively. The Si NW with a TEOS SiO2 layer on top had a larger strain than the Si NW surrounded only by thermal SiO2 .